PERANCANGAN KOMIK ANDHE ANDHE LUMUT BERDASARKAN RELIEF KISAH PANJI DI KOMPLEKS CANDI PENATARAN - Tegar Andito (DeKaVe, 2017)
Andhe Andhe Lumut is a folktale that derived from many versions of Panji tales. Andhe Andhe Lumut is the popular one amongst Indonesian, especially Javanese cultures. In popular culture, there are many works in various media that derived from Andhe Andhe Lumut story. Originally, as one of Panji tales, Andhe Andhe Lumut background story takes place at Kediri Kingdom era, but most of visual works like comics, picture story books, animations, drama costumes, etc use far more modern era style of traditional Javanese culture. Beside of that, from original text, Andhe Andhe Lumut folktale is designed for adult audiences, however most Indonesians have identified that folktale is a bedtime story for children. That’s why people can’t find visual works from Andhe Andhe Lumut story for adult audiences. As mentioned before, Panji tales have many versions. They are also already popular since Majapahit era. This is proven by carvings about some scene from Panji tales at Penataran Temple Complex which most of stuctures are built at Majapahit era. Panji tales themselves are semi fictional stories. Prince Panji or Inu Kertapati is inspired from King Kameswara II, seventh king of Kingdom of Kediri, and Princess Candra Kirana is inspired from Queen Kirana from Jenggala, but in Panji tales, their origins are opposite. Panji is from Jenggala and Candra Kirana is from Kediri. Ancient Javanese temple carvings could shows anything, but always showed environmental situations when the carvers live.”Teras Pendopo” building, where Panji tales carvings are located, was built at Majapahit era, when King Hayam Wuruk reigned. It is about 100 years after fall of Kediri, so the carvings are the closest visualization of Kingdom of Kediri daily life.Visualization of Andhe Andhe Lumut folktale based on original text and Panji tales characters at Penataran Temple Complex has never done before. Panji tales at Penataran Temple itself does not tell Andhe Andhe Lumut version of Panji. This comic design, if done properly can gives a new point of view about Andhe Andhe Lumut and can be the first comic of Andhe Andhe Lumut for adult audience with some historical accuracy.